2005
DOI: 10.1179/174328405x13994
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of nucleation and growth in Pb free Sn–Ag–Cu solder

Abstract: To investigate the minimum superheat necessary to solder components on printed circuit boards successfully using 95 . 5 wt-%Sn, 3 . 8 wt-%Ag, 0 . 7 wt-%Cu solder, experiments were carried out using separate solder balls of the type used in ball grid arrays. Significant differences in microstructure were observed depending on the peak temperature reached in the liquid on melting. On cooling, substantial undercooling was often observed, with values up to 18 K. Under some freezing conditions, the primary phase fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 5 publications
3
7
0
Order By: Relevance
“…After primary dendrite formation, solidification of the eutectic follows from the remaining liquid phase. [45][46][47] Both water-quenched bulk specimens and the small solder joints underwent significant undercooling during solidification. This undercooling resulted in a similar dendrite to eutectic region ratio of~50/50 for both specimen types.…”
Section: A Microstructure Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…After primary dendrite formation, solidification of the eutectic follows from the remaining liquid phase. [45][46][47] Both water-quenched bulk specimens and the small solder joints underwent significant undercooling during solidification. This undercooling resulted in a similar dendrite to eutectic region ratio of~50/50 for both specimen types.…”
Section: A Microstructure Characterizationmentioning
confidence: 99%
“…[1,5,6,[41][42][43][44][45][46][47][48] Microstructures for all three alloys and pure Sn in bulk form, cooled at 24°C/s and 0.1°C/s, are shown in Figure 2. In pure Sn, both water quenching (24°C/s) and furnace cooling (0.1°C/s) produced equiaxed Sn grains (Figure 2(a) and (e)), where the average grain sizes were 14 and 26 lm, respectively.…”
Section: A Microstructure Characterizationmentioning
confidence: 99%
“…4.3 Solidification process of Sn-Cu 6 Sn 5 and Sn-Ag 3 Sn binary eutectic structure Snugovsky et al 10) carried out experimental work on the solidification structure for Ball Grid Array condition using Sn-3.8Ag-0.7Cu alloy. They found that there were two binary eutectic structures in the specimen, i.e., Sn-Ag 3 Sn and SnCu 6 Sn 5 , which they named ''double binary''.…”
Section: Formation Of Eutectic Ag 3 Snmentioning
confidence: 99%
“…However, an unusual microstructure consisting of both Sn-Ag 3 Sn and Sn-Cu 6 Sn 5 binary eutectic structures is sometimes observed. 10) This unusual microstructure is known as a ''double binary eutectic'' structure. According to the phase diagram, these structures cannot be expected.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the most promising one is undoubtedly the Sn-Ag-Cu ternary alloy, which has advantages of good wetting property, superior interfacial properties, high creep resistance, low coarsening rate, and so on [2]. Recently, much research about the effect of the Ag content on several properties except thermal properties for a fixed Cu content in the Sn-Ag-Cu alloy have been performed [3][4][5][6].…”
Section: Introductionmentioning
confidence: 98%